Analisis E-learning Universitas Muhammadiyah Palembang Pada Mahasiswa Menggunakan Metode System Usability Scale - taufik hidayat; Suryayusra Suryayusra (Jurnal Pengembangan Sistem Informasi dan Informatika, 2022)
The exchange of information with technology makes the teaching and learning process easier. At Muhammdiyah University Palembang (UMP) has created a web called E-learning to facilitate students as an online learning tool and send assignments in the form of document and video files, research and knowledge that provides facilities and services that can be utilized for UMP students. This study aims to measure the level of satisfaction of E-Learning users as supporters in the learning process at UMP tertiary institutions. The method used for this study uses the System Usability Scale (SUS) method, where this method has 10 questions and 5 Usability Testing variables. After testing 85 UMP students of the Faculty of Law, the results according to the SUS scale have an average value of: 71.6. This result is included in the Acceptable category with Grade C and it can be said that UMP E-learning is good in terms of use and has an above average score. Keywords:UMP, E-learning, System Usability Scale